New on-water test for the assessment of blood lactate response to exercise in elite kayakers - Pilotto, A. M.; Rasica, L.; Scalise, G.; Annoni, S.; La Torre, A.; Marzorati, M.; Porcelli, S. (Medicine & Science in Sports & Exercise, 2019)
Purpose: Lactate thresholds are physiological parameters used to train athletes and monitor performance or training. Currently, the assessment of lactate thresholds in kayakers is performed in a laboratory setting utilizing specific ergometers; however, laboratory tests differ from on-water evaluation for several reasons. The aim of this study was to assess reliability and validity of a new on-water incremental test for the assessment of blood lactate response to exercise in flat-water kayakers. Maximal lactate steady state test (MLSS) was used as criterion measurement. Methods: Eleven junior (16.5 ± 1.9 yr) élite flat-water kayakers performed: i) an incremental cardiopulmonary test up to voluntary exhaustion on a stationary kayak ergometer to determine peak oxygen uptake; ii) an on-water 1000-m distance trial (T1000) to record best performance time and average speed (S1000); iii) two repetitions of on-water incremental kayaking test (WIK test); iv) several repetitions of on-water constant speed tests to determine MLSS. Speed, HR, and blood lactate concentrations were determined during on-water tests.